UVLEQoC: a ubiquitous virtual learning environment with quality of context - Nunes, Felipe Becker (2014)
U -Learning environments seek to collect information about users' preferences and needs to formulate its context and make adjustments to their content and interface to suit the user's profile, whereas in traditional VLEs, such as Moodle, this profile is hardly considered. Added to this, context information that are collected are characterized by being very volatile, which increases the probability that there are inconsistencies and inaccuracies. Based on this, the Quality of Context aims to treat this information with the application of quality standards that aim to create greater assurance that the context information reflects the momentary situation of the user. This paper presents a ubiquitous virtual learning environment, in which was developed three modules and integrated with Moodle, which was used as the basis for the development of this work. Parameters and metrics for Quality of Context are applied on the information collected in the environment, so that greater assurance can be created so that the context made the environment is appropriate to the preferences and needs of the user. Adaptations to the environment are performed using the Adaptive Hypermedia, and the types of information collected are cognitive user profile and your connection speed, which are captured through SEDECA 2.0 and U -SEA 2.0, respectively modules and that also suffered a restructuring in its mode of operation. Moreover, an automatic adaptation module provides the interface to the environment of use on mobile devices. As a result, testing software and users have shown that the environment UVLEQoC operated satisfactorily, based on the assessments made by the group of people who tested the modules and their operation. The questionnaire on the SUS and the developed modules, which included the validation of the technique through Cronbach's alpha, showed results within a range considered good, which reproduces the completion of the objectives proposed in this work, even if some difficulties and problems have been identified during development.